AppFusion: Interactive Appearance Acquisition Using a Kinect Sensor - Wu, Hongzhi; Zhou, Kun (Computer graphics forum, 2015)
We present an interactive material acquisition system for average users to capture the spatially varying appearance of daily objects. While an object is being scanned, our system estimates its appearance on‐the‐fly and provides quick visual feedback. We build the system entirely on low‐end, off‐the‐shelf components: a Kinect sensor, a mirror ball and printed markers. We exploit the Kinect infra‐red emitter/receiver, originally designed for depth computation, as an active hand‐held reflectometer, to segment the object into clusters of similar specular materials and estimate the roughness parameters of BRDFs simultaneously. Next, the diffuse albedo and specular intensity of the spatially varying materials are rapidly computed in an inverse rendering framework, using data from the Kinect RGB camera. We demonstrate captured results of a range of materials, and physically validate our system. We present an interactive material acquisition system for average users to capture the spatially varying appearance of daily objects. While an object is being scanned, our system estimates its appearance on‐the‐fly and provides quick visual feedback. We build the system entirely on low‐end, off‐the‐shelf components: a Kinect sensor, a mirror ball and printed markers. We exploit the Kinect infra‐red emitter/receiver, originally designed for depth computation, as an active hand‐held reflectometer, to segment the object into clusters of similar specular materials and estimate the roughness parameters of BRDFs simultaneously.